Assessment of Fluid Forces on Flooded Bridge Superstructures Using the SPH Method - Do, T. A.; Nguyen, T. H. (Civil Engineering Journal, 2024)
This paper presents a numerical simulation utilizing the Smoothed Particle Hydrodynamics (SPH) methodology to analyze the impact of water flow on bridge superstructures. The focus of the study is the Canh Nang bridge, which experienced significant damage during a severe flood in Vietnam. The SPH model accounts for flow morphology, velocity fields, and flow pressure around the submerged superstructure, providing insights into areas of high flow pressure and the water resistance coefficient (Cd). By employing modified dynamic boundaries for solid surfaces and the inflow-outflow conditions, the model effectively addresses fluid-bed and fluid-structure interactions. The results highlight elevated flow pressure on specific surface locations of the superstructure, while lower pressures are observed on the bottom surfaces and between adjacent girders. The calculated Cd values are evaluated against those from various bridge design standards, including the Indian code, Eurocode, AS5100, and TCVN 11823. This comparison reveals discrepancies and suggests the potential for refining current design practices. Future research directions include the experimental validation of SPH model results and the exploration of how structural parameters influence superstructure response during flood events. Doi: 10.28991/CEJ-2024-010-12-019 Full Text: PDF